2010
DOI: 10.1007/s00103-010-1193-x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in childhood and adolescence

Abstract: Numerous forms of therapy exist for the increasing number of obese children and adolescents in Germany, but these are heterogeneous and have not been evaluated. Access to health care, long- and short-term treatment outcome, as well as factors determining success of therapy were examined for the first time using standardized instruments to measure somatic and psychosocial variables. A total of 1,916 children aged 8-16 years from 48 (5 rehabilitation, 43 outpatient) institutions were examined. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
(21 reference statements)
4
10
1
2
Order By: Relevance
“…This corresponds with our previous results based on the same population [13], where we found a significant independent association between ADHD symptoms and overweight only in adolescent girls. The success of treatment for obesity is reduced by ADHD symptoms or impulsivity in most studies [29], [56], [57]. Girls are under stronger societal pressure to reduce weight and food intake than boys.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds with our previous results based on the same population [13], where we found a significant independent association between ADHD symptoms and overweight only in adolescent girls. The success of treatment for obesity is reduced by ADHD symptoms or impulsivity in most studies [29], [56], [57]. Girls are under stronger societal pressure to reduce weight and food intake than boys.…”
Section: Discussionmentioning
confidence: 99%
“…2a-c). Previous studies indicated that a lower BMI at the beginning of a LI is one predictor of success as measured by BMI SDS [10,11]. However, the indication to participate in an outpatient or inpatient LI depends on obesity degree and existing risk factors or comorbidities (table 4) [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In a study analyzing 1,916 children (8 to <16 years of age) from 48 institutions (5 rehabilitation, 43 outpatient centers) in Germany, the short-term success (1-year-follow-up) was as lower as more obese the children were [10]. The authors also stated a higher success rate in younger children [10]. Similar results were indicated by another study with 2-year follow-up [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the follow-up rates in our study may be considered as somewhat satisfying compared to other studies in the field. In an observational follow-up study of different treatment programmes in Germany, loss to follow-up was already 58.6% one year after the end of treatment and 72.5% after initial inpatient treatment [65]. In an attempt to compensate for our nevertheless large and presumably biased loss to follow-up, we consequently used an intention to treat analysis with baseline values imputed for missing values at follow-up which eventually handles dropouts as a “failure.” Thus, the estimates of treatment effects are considered conservative in the sense that true effects might be slightly better than our estimates.…”
Section: Discussionmentioning
confidence: 99%